2006
DOI: 10.1074/jbc.m511348200
|View full text |Cite
|
Sign up to set email alerts
|

Integration Requires a Specific Interaction of the Donor DNA Terminal 5′-Cytosine with Glutamine 148 of the HIV-1 Integrase Flexible Loop

Abstract: Integration is essential for retroviral replication and gene therapy using retroviral vectors. Human immunodeficiency virus, type 1 (HIV-1), integrase specifically recognizes the terminal sequences of each long terminal repeat (LTR) and cleaves the 3-end terminal dinucleotide 5-GT. The exposed 3-hydroxyl is then positioned for nucleophilic attack and subsequent strand transfer into another DNA duplex (target or chromosomal DNA). We report that both the terminal cytosine at the protruding 5-end of the long term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
60
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 45 publications
3
60
0
Order By: Relevance
“…Preparation of Recombinant HIV-1 IN, DNA Oligonucleotides, and Cross-linked Products-Full-length IN and mutant proteins were expressed in E. coli and purified as described previously (35). The catalytic activities of recombinant proteins were monitored according to the reported procedure (35).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Preparation of Recombinant HIV-1 IN, DNA Oligonucleotides, and Cross-linked Products-Full-length IN and mutant proteins were expressed in E. coli and purified as described previously (35). The catalytic activities of recombinant proteins were monitored according to the reported procedure (35).…”
Section: Methodsmentioning
confidence: 99%
“…The catalytic activities of recombinant proteins were monitored according to the reported procedure (35).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The molecule dynamics simulation results of full-length integrase-DNA complex suggested that the catalytic loop played crucial role during integration process (De Luca et al, 2005). It had been reported that the residue Gln148 of HIV-1 integrase was critical for strand transfer (Johnson et al, 2006).…”
Section: Comparison Of the Two Different Dimersmentioning
confidence: 99%